Effect of familial mediterranean fever on ivf outcome: a retrospective case series - Nafiye Karakas Yilmaz; Mustafa Kara; Metin Kaba; Bugra Coskun; Selcuk Erkilinc; Salim Erkaya (Acta Clinica Croatica, 2016)
Although the in vitro fertilization-intra-cytoplasmic sperm injection (IVF-ICSI) has been utilized widely, the management in patients with an autoimmune disease is still a challenge. The aim of this study was to demonstrate IVF-ICSI outcomes in infertile women with familial Mediterranean fever (FMF). Patient data were collected from the cases registered from January 2006 until January 2014. A total of 6152 assisted reproductive technology (ART) cycles were analyzed retrospectively in the Ankara Zekai Tahir Burak Women’s Health Education and Research Hospital. Ten infertile women with FMF were included in the study. Baseline clinical and laboratory characteristics were collected and perinatal outcomes evaluated. The mean age (years), duration of infertility (years) and body mass index (kg/m2) were 29.9±5.3, 5.7±5.3 and 27.9±5.7, respectively. The mean baseline follicle-stimulating hormone (FSH; IU/L), estradiol (E2; pg/mL) and antral follicle count were 7.0±2.4, 48.1±15.8 and 7.9±2.9, respectively. The distribution of ovarian response was heterogeneous. Fourteen cycles in ten patients were evaluated. Embryo transfer could be achieved in only ten cycles. Three out of ten patients became pregnant. No adverse perinatal outcome was observed. Our findings indicate that FMF might have no impact on ART cycles.